A mixed method examination: how stigma experienced by autistic adults relates to metrics of social identity and social functioning - Marion, Alex; Bowman, Karrah; Thomas, Gina; Harrison, Ashley J. (Frontiers in Psychiatry, 2023)
A recent meta-analysis reveals almost half of autistic individuals experience some form of victimization in their lifetime, including bullying and other forms of stigma. Research among caregivers of autistic individuals demonstrates that stigma can have a long-lasting impact on other aspects of a social identity, such as self-esteem, but less research has specifically examined this among autistic adults themselves, in spite of research suggesting these are likely constructs that contribute to the internalization of stigma and subsequent mental health consequences. The current study used a mixed method approach to assess the relation between stigma and several components of social identity and social functioning. More specifically, among 45 autistic young adults, three dimensions of self-reported stigma (discrimination, disclosure, and positive aspects) were examined in relation to self-esteem, self-efficacy, social satisfaction and adaptive social functioning. Quantitative analyses revealed higher reported discriminative and disclosure stigma were significantly associated with lower self-efficacy. Increased experience with all types of stigma were all associated with lower social satisfaction. Greater reported disclosure stigma was also associated with lower self-esteem. Qualitative interviewing among eight autistic young adults helped to better understand the nature of stigma and the impact of these experiences. Thematic analysis of the qualitative data revealed that all of the participants experienced stigma in the form of exclusion or isolation and that a majority also experienced verbal bullying. Many of the negative interactions came from educators, peers, and family members. Most participants indicated that these stigmatizing interactions directly contributed to decreased social satisfaction, diminished self-efficacy, and lowered self-esteem. A greater understanding of the negative consequences of stigma can inform efforts to increase awareness and acceptance of autism.